2010
DOI: 10.1007/s10157-010-0264-5
|View full text |Cite
|
Sign up to set email alerts
|

Amino terminal cleavage of PTH(1–84) to PTH(7–84) is regulated by serum calcium concentration via calcium-sensing receptor in hemodialysis patients

Abstract: Whereas in the absence of calcimimetics cleavage of N-terminal PTH was regulated by serum calcium concentration, this regulation was abolished in the presence of calcimimetics. This suggests that cleavage of N-terminal PTH is regulated by calcium concentration via a calcium-sensing receptor and that calcimimetics may have a novel effect to reduce PTH level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In the present clinical trial, we showed that cholecalciferol treatment was efficient to normalize the serum levels of 25(OH)D and decrease PTH levels in patients supplemented compared to placebo group, suggesting that adequacy of vitamin D status might have modulated synthesis this hormone in parathyroid cells and this effect might have contributed to lower bone reabsorption [12]. In respect to the serum FGF-23 in cholecalciferol group, the significant difference detected by the group-time interaction analysis might be due to the higher production of this hormone by osteocytes, since vitamin D administration upregulates FGF-23 [13, 28].…”
Section: Discussionmentioning
confidence: 92%
“…In the present clinical trial, we showed that cholecalciferol treatment was efficient to normalize the serum levels of 25(OH)D and decrease PTH levels in patients supplemented compared to placebo group, suggesting that adequacy of vitamin D status might have modulated synthesis this hormone in parathyroid cells and this effect might have contributed to lower bone reabsorption [12]. In respect to the serum FGF-23 in cholecalciferol group, the significant difference detected by the group-time interaction analysis might be due to the higher production of this hormone by osteocytes, since vitamin D administration upregulates FGF-23 [13, 28].…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, circulating 7-84 PTH fragments are generated not only by the peripheral metabolism of 1-84 PTH, but they are also secreted, in a Ca-dependent manner, by the PT glands; it appears that the CaSR is involved [54,58]. The results of initial studies investigating the clinical role of the 1-84 PTH/7-84 PTH ratio, in which a low ratio (relatively high proportion of 7-84 PTH) was associated with low bone turnover, have proven to be inconsistent and not clinically useful [59][60][61].…”
Section: Pth Fragmentsmentioning
confidence: 97%
“…Regarding the determination method, despite the available immunoassays showing important differences in absolute values (37), we observed that the relative change induced by cinacalcet treatment was fully comparable between the 3 kits used (2 of them measuring iPTH and 1 specific for PTH 1-84, ie, whole PTH, also known as biointact). Previous studies had already suggested that cinacalcet reduces not only iPTH but also whole PTH and the whole PTH to iPTH ratio (38) and that it also changes the regulation of N-terminal PTH cleavage by calcium concentration (39,40).…”
mentioning
confidence: 99%